THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE WORK DISCIPLINE - Syafrudin, Oding; Junaedi, Jujun; Maulana, Yasir (Universitas Kuningan, 2024)
Based on preliminary observations, indications of problems in this study are that employee work discipline is still low. The purpose of this study was to determine the effect of leadership and work motivation on employee discipline at PT Bawang Kuningan Kencana. The method used in this research is quantitative descriptive verification method. The sampling technique with total sampling so that the sample is all the population is sampled as many as 75 employees of PT Bawang Kuningan Kencana. The data processing technique used is multiple linear regression test. The results of hypothesis testing show that there is a significant influence between transformational leadership on employee work discipline. There is a significant influence between work motivation on employee work discipline. Transformational leadership and work motivation together have a positive effect on employee work discipline.